Essential oil composition of Hyssop (Hyssopus officinalis L.) under salt stress at flowering stage. Issue 5 (2nd September 2016) - Jahantigh, Omolbanin; Najafi, Farzaneh; Naghdi Badi, Hassanali; Khavari-Nejad, Ramazan Ali; Sanjarian, Forough
Abstract: The major environmental abiotic stresses are soil salinity and droughts, the high levels of sodium which are toxic to most varieties of plants species, and more importantly affect plant growth and limit the plants yield capacity. Medicinal plants of recent have received much attention, Hyssopus officinalis has been known as a culinary and medicinal herb for hundreds of years, it is cultivated globally. At presently there is no available research on this plants reaction to soil salinity levels. This study will endeavor to examine in length the effects of salinity on the essential oil contents and composition of H. officinalis . The salinity treatments were five levels at: 0, 2, 4, 6 and 8 dSm -1 saline water from the Hos-e-sultan Lake. The hydrodistilled volatile oils derived from aerial part of H. officinalis at Flowering Stage were investigated by gas chromatography and GC–mass spectrometry. With increasing of salinity essential oil obtained of aerial parts increased. The maximum essential oil amount obtained in EC 6 dSm -1 . Thirty-nine components were characterized and isolated, representing 95–99% of the total components detected. The major components identified in the control group and in the treated plants were cis - pinocamphone, β-pinene, β-phellandrene, pinocarvone, myrtenol, elemol, myrcene, linalool and germacrene D.